1

For instance in the following example

Let be F={AB→C, B→D, CD→E, CE→GH, G→A}

Do we have AB→G?

We don't have any functional dependencies.

I am able to show a functional dependency when it works but how to show a counterexample when it doesn't?

1 Answer 1

2

To find if the functional dependency AB→G is implied by F you should find the closure of the attributes AB under F, i.e. AB+.

These are the steps:

AB+ = AB
      ABC     (using AB→C)
      ABCD    (using B→D)
      ABCDE   (using CD→E)
      ABCDEGH (using CE→GH)

and since G belongs to AB+, then AB→G can be derived from F.

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.